A Core System of Local Governance into Public Health: An In-Depth Assessment of Rogi Kalyan Samitis of Health Facilities in Gujarat - Narkhede, Kiran M; Shah, Harsh D; Parmar, Priyank A; Patel, Randhir R; Vyas, Tejas N; Dave, Paresh (National Journal of Community Medicine, 2017)
Introduction: National Health Mission (NHM) was envisaged with the core objective of decentralization and health systems strengthening. The study tried to assess the utilization pattern of untied fund allocated to Rogi Kalyan Samitis of community health centers and primary health centres across the Gujarat. Methodology: Routine reporting of the Financial Management Reports was analysed to assess utilization pattern of financial year 2013-14. Results: RKS is predominantly using the fund to cover up the local needs at facility levels like outsourcing of the staff (10%), minor civil works (12%), drugs-consumables and logistics (24%). The contingency expenditure takes a large section too. Miniature part has been utilised for the day to day expenses of the facilities like printing, linen & training. This can be attributed to structural and managerial role of the system. Moreover NHM need to improve the mechanism for benefitting local community and utilization of the funds through RKS. Conclusion: Study emphasize a need for devising strategies and planning to fulfil the civil works, shortfall of staff, drugs procurement & efficient supply chain management to overcome the burden. Knowledge base of members needs to be strengthened for a clear understanding of the objectives, functioning and roles of RKS.